Design Aspects of Electric Motors for Borehole Investigating Mechatronic System - Gečys, S.; Smolskas, P. (Elektronika ir Elektrotechnika, 2007)
The design aspects and peculiarities of the electric motor for borehole investigating mechatronic system which are related to the specific operating conditions of these motors are presented. Such borehole motors have not the concrete fixed rated operation point, which is characteristic for the traditional electrics motors, therefore the usual rated parameters can be changed into the integral parameter, which characterize the borehole motor in entire slip range from 0 up to 1. The electromagnetic estimation of the main possible two-pole two-phase and three-phase stator windings for the borehole motors, of which the slot number of the stator is 8 or 12, is presented. The stator windings from the electromagnetic point of view are evaluated considering the winding factor and quality index, which characterize the weight of the relative magnetomotive force higher harmonic of the stator winding. The increased main demands for the stator windings of the borehole motors are discussed. Bibl. 7 (in English; summaries in English, Russian and Lithuanian).